Remodeling of the dermal-epidermal junction in bilayered skin constructs after silencing the expression of the p.R2622Q and p.G2623C collagen VII mutants - Steplewski, Andrzej (Connect Tissue Res, 2012)
The integrity of skin depends on a complex system of extracellular matrix molecules that form a biological scaffold. One of its elements is the dermal basement membrane that provides a link between the epidermis and the dermis. Mutations in collagen VII, a key component of the dermal membrane zone, are associated with dystrophic epidermolysis bullosa. Although it has been proposed that silencing the mutated COL7A1 allele is a promising approach to restore the dermal basement membrane zone formed in the presence of collagen VII mutants, limitations exist to testing this proposal. Here, we employed a model that utilized skin-like constructs in which engineered collagen VII mutant chains harboring the R2622Q or G2623C substitution were expressed conditionally, but the wild type chains were expressed unconditionally. We demonstrated that switching off the production of the mutant collagen VII chains in skin constructs restores the organization of collagen VII and laminin 332 deposits in the dermal-epidermal junction to the level of control. We also demonstrated that remodeling of collagen IV deposits was not fully effective after silencing the expression of collagen VII mutants. Thus, our study suggests that while silencing mutant alleles of COL7A1 may repair critical elements of the affected dermal basement membrane, it may not be sufficient to fully remodel its entire architecture initially formed in the presence of the mutant collagen VII chains.